2004
DOI: 10.1038/sj.ejcn.1601858
|View full text |Cite
|
Sign up to set email alerts
|

Detection and recognition thresholds to the 4 basic tastes in Mexican patients with primary Sjögren's syndrome

Abstract: Background: Primary Sjögren's syndrome (pSS) is a chronic autoimmune disease characterized by inflammatory lymphocytic infiltration of the salivary glands, leading to dryness of the mouth (xerostomia). It has been postulated that xerostomia is the preceding stage for the development of alterations in taste acuity (dysgeusia) in this type of patients. Objectives: To determine detection and recognition thresholds to the 4 basic tastes (sweet, salty, sour and bitter) in pSS patients and compare them to a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
(32 reference statements)
1
38
1
Order By: Relevance
“…About 77% of patients had at least one taste threshold below the 10th percentile of controls, and among these patients 78% had low sensitivity for two or more taste qualities [12]. A more recent report by Gomez et al (2004) also showed that Sjögren's syndrome patients were clearly hypogeusic for bitter and sour tastes and mildly hypogeusic for sweet and salty tastes [14]. Together, these human studies demonstrate that taste abnormalities can develop in this autoimmune disease.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…About 77% of patients had at least one taste threshold below the 10th percentile of controls, and among these patients 78% had low sensitivity for two or more taste qualities [12]. A more recent report by Gomez et al (2004) also showed that Sjögren's syndrome patients were clearly hypogeusic for bitter and sour tastes and mildly hypogeusic for sweet and salty tastes [14]. Together, these human studies demonstrate that taste abnormalities can develop in this autoimmune disease.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that Sjögren's syndrome patients exhibit reduced sensitivities to bitter, sour, sweet, and salty taste compounds [12], [13], [14]. Henkin et al (1972) reported that 90% of Sjögren's syndrome patients in their study had bitter and sour detection and recognition thresholds elevated above the normal levels, whereas 72% and 38% of patients had salt and sweet thresholds above the normal levels, respectively [13].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Low concentrations of one tastant may be misidentified as another (Pilkova et al, 1991); to avoid this potential confounding effect, subjects were informed as to the taste stimulus. In addition, detection thresholds (i.e., the ability to detect the presence of a tastant, rather than what the taste is), although often lower than recognition thresholds, are also more variable between subjects (Gomez et al, 2004). Tastants were applied in solution to the tip of the tongue, using a cotton bud saturated with the solution at room temperature, and placed on the tongue for ϳ5 s (Prutkin et al, 1999).…”
Section: Methodsmentioning
confidence: 99%